Indian Knowledge System and National Education Policy (Nep) 2020 - Das, Ranjit Kumar (Integrated Journal for Research in Arts and Humanities, 2024)
Knowledge is the supreme value. Indian knowledge tradition is a pernnial flow of the Ganga. Ganga is a symbol of purity and liberationas it descended from heaven to give moksha to the people of yogabhumi, Bharata. Indian Knowledge System aspired to know everything that the mind can comprehend from tiny atoms to the universe. India has a glorious tradition of spirituality propagated by a long line of rishis. The teachings of the sages have an eternal relevance and unleashed the creativity of the Indian culture over a wide spectrum-literature, medicine, music, dancing art, painting, sculpture, mythology, ethics, astronomy, mathematics, grammar, metaphysics, epistemology, ontology, yoga, phiplosophy, psychology and economics. This explosion of creativity has enriched Indian culture and upliftment the human soul. Vedas are the oldest and richest source of Indian Knowledge Systems based on spiritual knowledge. The Supreme Creator creates the cosmos, the creative potency descends among the created beings to assist the Supreme Creator in the manifestation of the material worlds. Universities are temples of knowledge where ideas, innovations, and skills are nurtured. The National Education Policy 2020 is the synthesis of knowledge and education and from the teaching of humanity and values, India is Vishwaguru.